Central and Northern European caterpillar assemblages show strong phylogenetic structure. (7th November 2021) - Strutzenberger, Patrick; Fiedler, Konrad
Abstract: Phylogenetic diversity metrics have been used to tackle an increasing number of questions in ecology and evolutionary biology. Here we present a novel use of phylogenetic diversity metrics namely the investigation of insect herbivore assemblages on select plant species in order to investigate possible drivers shaping the phylogenetic structure of those assemblages. We investigated the phylogenetic structure of lepidopteran herbivore assemblages on 208 species of central European vascular plants. A dataset of 2, 553 species of Lepidoptera from 68 families, comprising 8, 584 individual herbivore‐host associations, was analysed for patterns of phylogenetic α‐ and β‐diversity in relation to plant growth form, plant phylogeny and the accumulation of some characteristic major classes of secondary plant metabolites. Distinct patterns of phylogenetic β‐diversity were detected when plants were partitioned into three growth form categories (graminoid, herbaceous and woody). In contrast, groupings of plants according to higher taxa or key secondary metabolites did not yield similarly clear patterns. Notable exceptions were assemblages on graminoid plants, especially those containing silica, which could be distinguished by both plant phylogeny and their phytochemical characteristics. Additionally plants containing highly toxic glucosinolates (all of the family Brassicaceae) harbour highly distinct lepidopteran assemblages. Phylogenetic α‐diversity of associated caterpillars differed greatly between graminoid, herbaceous and woody plants. Assemblages on graminoid plants were found to be the most phylogenetically clustered, followed by herbs and woody plants which showed the least degree of phylogenetic clustering. In conclusion, our results indicate that the phylogenetic structure of the investigated herbivore assemblages in the nemoral and boreal zones of the Western Palaearctic region is most heavily influenced by plant growth form while categories derived from higher plant systematics or classifications reflecting secondary metabolites leave far less signal at this macroecological scale. The approach taken in this study proved to be very successful in identifying patterns in the phylogenetic structure of herbivore assemblages. Our findings are in line with the 'classical' plant apparency hypothesis. Plant secondary compounds were found to have only limited explanatory power on our scale of analysis. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.